Pro TypeScript Application-Scale JavaScript Development - Fenton, Steve (Apress : Imprint: Apress, 2014)
JavaScript is everywhere, both as a pure language and in popular libraries like Angular, jQuery and Knockout, but users of modern object-oriented languages like Java and C# often find JavaScript frustrating to use and hard to extend to large-scale applications. TypeScript is an innovative open source language from Microsoft that combines powerful language features and enhanced tooling support with the key attractions of JavaScript as a flexible, dynamic language that can run in any browser and on any operating system. Pro TypeScript tells you everything you need to know about this exciting new language and how to use it in your applications. Starting with an introduction to the language and its features, the book takes you through some of the major features of TypeScript in depth, from working with the type system through object-orientation to understanding the runtime and the TypeScript compiler. The book then covers some of the factors you need to consider when running a TypeScript application in the browser, including interacting with the DOM, making asynchronous requests, and working with useful browser APIs, followed by a demonstration of server-side TypeScript using the popular Node.js framework. Because TypeScript compiles to plain JavaScript, exception handling, memory management and garbage collection can differ depending on where you run your program, so these topics get a chapter to themselves. You'll also find out how to include popular JavaScript frameworks in your applications, so you can combine the benefits of TypeScript with some of the best JavaScript code that's already out there waiting to be used. The final chapter gives an overview of automated testing for TypeScript applications. Pro TypeScript offers a balanced and practical guide to a language that will transform your experience of JavaScript development.